Eficácia de um protocolo de tratamento com estimulação intracraniana por corrente contínua e fisioterapia ocular no movimento sacádico de adultos e idosos com Parkinson - Lara, Bernardo Amarante de (2022)
Saccadic eye movement dysfunction is common in people with Parkinson's Disease (PD), however, as therapeutic practices that include Physiotherapy are incipient to determine your assistance for this therapy. This pioneering study in the area does not aim to integrate theoretical knowledge about motor development and behavior with the use of technologies and a new work methodology in the field of Physiotherapy, it had as its general objective to develop a protocol of care with eye training and transcanial direct current stimulation (tDCS) and to verify its influence on the performance of eye saccadic movement in people with PD. As specific objectives, to investigate the effect of tDCS with eye training on aspects and functional, cognitive gait and training in the pre-intervention periods and quality of eye saccadic movement can be modulated by tDCS. To respond to the objectives elaborated in the form of scientific publications, empirical articles. The first production, “The Influence of Transcranial Direct Current Stimulation on Saccadic Eye Movement: Systematic Review” is in Chapter 3. The second production, Transcranial Stimulation Protocol and Ocular Physiotherapy in Elderly People with Parkinson's Disease is in Chapter 4 , aimed to propose a care protocol with eye training and Transcranial Direct Current Stimulation (tDCS) and to control its influence on the execution of saccadic eye movement, in aspects such as gait, balance and functionality, in people with PD. This is a report of two cases of patients with a diagnosis of PD confirmed by the neurologist, with the ability to walk, normal or corrected visual acuity and preserved cognitive ability. The services were associated with an tDCS associated with oculomotor exercises. We used the Mini-Mental State Examination, the UPDRS Scale, the “Time Up and Go Test” and the “Berg Balance Scale” as evaluative instruments, in addition to the “Eletronystagmography” exam. It was possible to verify the ability of the scores in the sense of global improvement, but with different results in the assessment of eye movement. The results are promising and motivate the replication of future studies so that it can help in the therapy of people with PD.